Firms' measures in response to labor markets and technological change: a study on local skilled workers participation at multinational companies / Hadijah Iberahim - Iberahim, Hadijah (Faculty of Business and Management, 2013)
Identifying reasons and needs for skilled workers is an imperative managerial issue for multinational companies (MNCs) operating in foreign countries. This study examines factors that influence demand for skills at firm-level in response to external forces such as labor markets and technological change. The issue is important and urgent in the case of Malaysia, whereby the supply of skills is critically insufficient for high technology manufacturing MNCs. As an attempt to provide an insight into the issue of increasing demand for skilled workers, a comparative study on two Malaysian-based Japanese MNCs was undertaken. This exploratory study takes a qualitative approach to analyze data covering the period from 1980 to 2012. Findings show that besides the needs for technological change and constraints in labor markets, differences in firm measures have resulted to increasing demand for skilled workers. These findings have significant theoretical and practical implications to international human resource management studies. The study extends knowledge on the impact of MNCs activities on human capital development